2021
DOI: 10.1371/journal.pone.0254357
|View full text |Cite
|
Sign up to set email alerts
|

A novel olfactory threshold test for screening cognitive decline among elderly people

Abstract: Olfactory impairment is associated with dementia and is a potential early biomarker of cognitive decline. We developed a novel olfactory threshold test called Sniff Bubble using rose odor-containing beads made with 2-phenylethyl alcohol. We aimed to define cut-off scores for this tool to help identify cognitive decline among elderly people. In total, 162 elderly people (mean age ± SD: 73.04 ± 8.73 years) were administered olfactory threshold and neurocognitive tests. For analyses, we divided the participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…In terms of the diagnostic utility of the DESK assessment tool used in this study, we found a high diagnostic utility with all combinations. Previous studies have demonstrated associations between cognitive function decline and olfactory function, including in Japanese and Asian populations, and indicate that impairment in olfactory discrimination can predict future cognitive decline [ 20 , 27 , 28 ]. These results suggest that the greater a patient's decline in cognitive function, the higher the possibility of reduced olfactory function occurring due to cerebral limbic system or olfactory nerve neuropathy [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the diagnostic utility of the DESK assessment tool used in this study, we found a high diagnostic utility with all combinations. Previous studies have demonstrated associations between cognitive function decline and olfactory function, including in Japanese and Asian populations, and indicate that impairment in olfactory discrimination can predict future cognitive decline [ 20 , 27 , 28 ]. These results suggest that the greater a patient's decline in cognitive function, the higher the possibility of reduced olfactory function occurring due to cerebral limbic system or olfactory nerve neuropathy [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used odor identification test is the University of Pennsylvania Smell Identification Test (UPSIT), however, it takes too long to administer by using 40 scents. Furthermore, too much odor identification can be affected by differences in region, culture, and individual experiences, so it is complicated to use as a screening test for the elderly ( Kim et al, 2020 , 2021 ). The “Sniffin’ Sticks” Test (SST) is another widely used odor test, but its applicability is limited because of the high cost and the regional-cultural differentiation of odor recognition ( Demir et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Early detection of dementia provides a number of advantages, including the prevention of risk factors and timely appropriate treatments [ 5 , 6 ]. Although AD is currently incurable, there are pharmacologic and cognitive treatment options that alleviate dementia symptoms and slow disease progression [ 7 ]. Moreover, patients can establish their treatment plans for comorbid diseases in advance.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there are no established peripheral biomarkers that are simple, inexpensive, and readily available in clinical settings. Olfactory and retinal changes have been suggested as potential peripheral biomarkers of AD [ 7 , 16 ]. Kim et al developed a novel olfactory threshold test for dementia screening that adequately detected cognitive decline in older patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation